Thermoplastic resin composition
A graft copolymer resin enhances the solvent resistance and impact resistance of thermoplastic resins by graft polymerizing an aromatic vinyl monomer onto a rubber-like polymer with (meth)acrylic acid ester units, improving the chemical resistance of industrial and home appliance products.
Patent Information
- Application Number
- JP2020206844
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-12-14
AI Technical Summary
There is a need for rubber-reinforced thermoplastic resins with improved chemical resistance, particularly solvent resistance, to enhance the quality of industrial and home appliance products that come into contact with various chemicals.
A graft copolymer resin is produced by graft polymerizing a vinyl monomer containing an aromatic vinyl monomer onto a rubber-like polymer with a structural unit derived from (meth)acrylic acid ester, resulting in a thermoplastic resin composition with enhanced solvent resistance, impact resistance, and fluidity.
The thermoplastic resin composition exhibits improved solvent resistance, weather resistance, and maintains impact resistance and fluidity, as demonstrated by specific contact angle measurements and resistance to mixed solvents.
Smart Images

Figure 0007601627000001 
Figure 0007601627000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition. [Background technology]
[0002] Rubber-reinforced thermoplastic resins are excellent in moldability, impact resistance, mechanical strength, etc., and are widely used in industrial parts and household electrical appliances. In these applications, they often come into contact with various chemicals, detergents, etc., and so it is necessary to impart chemical resistance to the rubber-reinforced thermoplastic resins.
[0003] For example, Patent Documents 1 to 3 disclose that a rubber-reinforced thermoplastic resin obtained by graft-polymerizing a specific monomer onto an acrylic rubber-like polymer has excellent chemical resistance. Note that the rubber-reinforced thermoplastic resin is often used as a thermoplastic resin composition further containing other thermoplastic resins. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-173361 [Patent Document 2] Japanese Patent Application Publication No. 8-113689 [Patent Document 3] Japanese Patent Application Publication No. 9-316291 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for rubber-reinforced thermoplastic resins with improved chemical resistance in order to improve product quality, etc. Therefore, an object of the present invention is to provide a thermoplastic resin composition containing a rubber-reinforced thermoplastic resin with improved chemical resistance, particularly improved solvent resistance. [Means for solving the problem]
[0006] As a result of intensive research conducted by the present inventors in order to solve the above problems, it has been found that the above problems can be solved by the inventions described in [1] and [2] below. [1] A thermoplastic resin composition comprising a graft copolymer resin obtained by graft polymerizing a vinyl monomer including an aromatic vinyl monomer onto a rubber-like polymer including a structural unit derived from a (meth)acrylic acid ester, and a thermoplastic resin, A thermoplastic resin composition, in which when a mixed solvent of hexane and ethanol (mass ratio 1:1) is dropped onto a molded article formed from the thermoplastic resin composition, the contact angle 0.2 seconds after the drop is dropped is 15 degrees or more. [2] The thermoplastic resin composition according to [1], wherein the difference between the contact angle 0.2 seconds after application and the contact angle 10 seconds after application is 12 degrees or more. Effect of the Invention
[0007] According to the present invention, it is possible to provide a thermoplastic resin composition containing a rubber-reinforced thermoplastic resin having improved solvent resistance. Furthermore, the thermoplastic resin composition of the present invention has sufficient weather resistance, impact resistance and flowability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, preferred embodiments of the present invention will be described. In this specification, the term "(meth)acrylic acid ester" refers to an acrylic acid ester or a methacrylic acid ester, and the same applies to similar expressions such as "(meth)acrylate".
[0009] The thermoplastic resin composition of the present embodiment contains a graft copolymer resin obtained by graft polymerizing a vinyl monomer including an aromatic vinyl monomer onto a rubber-like polymer including a structural unit derived from a (meth)acrylic acid ester, and a thermoplastic resin.
[0010] Examples of the rubbery polymer include (meth)acrylic rubbery polymers mainly composed of (meth)acrylic acid ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; composite rubbery polymers of butadiene rubbery polymer / (meth)acrylic rubbery polymer; composite rubbery polymers of silicone rubbery polymer / (meth)acrylic rubbery polymer, etc. These may be used alone or in combination of two or more.
[0011] Among these rubbery polymers, from the viewpoint of further improving the solvent resistance, a (meth)acrylic rubbery polymer is preferred, a (meth)acrylic rubbery polymer containing a structural unit derived from an alkyl ester of (meth)acrylic acid is more preferred, and a (meth)acrylic rubbery polymer containing a structural unit derived from an alkyl ester of (meth)acrylic acid having 4 or more carbon atoms in the alkyl group is even more preferred. The content of the structural unit derived from an alkyl ester of (meth)acrylic acid (particularly an alkyl ester of (meth)acrylic acid having 4 or more carbon atoms in the alkyl group) in the (meth)acrylic rubbery polymer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, from the viewpoint of further improving the solvent resistance. The upper limit of the content of the structural unit derived from an alkyl ester of (meth)acrylic acid in the (meth)acrylic rubbery polymer is not particularly limited, but can be, for example, 95% by mass or less.
[0012] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate.
[0013] The rubber-like polymer may be crosslinked with a crosslinking agent, such as divinylbenzene, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, diallyl phthalate, dicyclopentadiene di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol hexa(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triallyl cyanurate, and triallyl isocyanurate.
[0014] The rubber-like polymer may have a structural unit derived from a monomer other than the above-mentioned (meth)acrylic acid alkyl ester, such as a structural unit derived from a conjugated diene monomer, an aromatic vinyl monomer, or a vinyl cyanide monomer.
[0015] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2-chloro-1,3-butadiene, chloroprene, 2-methyl-1,3-butadiene, and 2,3-dimethyl-1,3-butadiene, and these can be used alone or in combination.
[0016] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, paramethylstyrene, bromostyrene, etc., and one or more of these can be used.
[0017] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, ethacrylonitrile, fumaronitrile, etc., and one or more of these can be used.
[0018] The content of the structural units derived from the conjugated diene monomer, aromatic vinyl monomer or vinyl cyanide monomer in the rubbery polymer can be, for example, 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less. When the rubbery polymer contains these structural units, the lower limit of the content is not particularly limited, but each can be, for example, 1% by mass or more.
[0019] The rubber-like polymer can be produced by a conventional method, for example, emulsion polymerization, which may be carried out in the presence of a polymerization initiator, an emulsifier, a polymerization regulator, etc.
[0020] Examples of the polymerization initiator include water-soluble polymerization initiators such as potassium persulfate, sodium persulfate, and ammonium persulfate, and oil-soluble polymerization initiators such as cumene hydroperoxide, benzoyl peroxide, t-butyl hydroperoxide, acetyl peroxide, diisopropylbenzene hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.
[0021] Examples of the emulsifier include carboxylates, sulfates, sulfonates, etc. Specific examples of emulsifiers that are preferably used include potassium oleate, dipotassium alkenyl succinate, sodium rosinate, potassium rosinate, disproportionated sodium rosinate, potassium disproportionated rosinate, sodium dodecylbenzenesulfonate, etc.
[0022] Examples of the polymerization regulator include alkyl mercaptans such as n-dodecyl mercaptan and t-dodecyl mercaptan.
[0023] From the viewpoint of improving the impact resistance of the graft copolymer resin, the above rubber-like polymer preferably has a gel content of 75 to 90%. The gel content of the rubber-like polymer is measured, for example, by the method described later in the Examples.
[0024] From the viewpoint of the balance between impact resistance and fluidity, the graft copolymer resin preferably contains the rubber polymer in an amount of 10 to 90 mass %, more preferably 30 to 80 mass %, and even more preferably 40 to 70 mass %.
[0025] The vinyl monomer used in the graft polymerization includes an aromatic vinyl monomer. The vinyl monomer preferably further includes a vinyl cyanide monomer and / or an alkyl (meth)acrylate ester. The aromatic vinyl monomer, the vinyl cyanide monomer, and the alkyl (meth)acrylate ester may be the same as those described above.
[0026] The content of the aromatic vinyl monomer used in the graft polymerization can be, for example, 50 to 90 mass%, preferably 55 to 85 mass%, more preferably 60 to 80 mass%, based on the total amount of vinyl monomers. The content of the vinyl cyanide monomer used in the graft polymerization can be, for example, 10 to 40 mass%, preferably 15 to 35 mass%, more preferably 20 to 30 mass%, based on the total amount of vinyl monomers.
[0027] The content of the (meth)acrylic acid alkyl ester in the vinyl monomer used in the graft polymerization is preferably 5 to 30 mass % based on the total amount of the vinyl monomer, from the viewpoint of further improving the solvent resistance.
[0028] The graft copolymer resin can be produced by a conventionally known method, and examples of the polymerization methods that can be used include emulsion polymerization, suspension polymerization, and bulk polymerization. When emulsion polymerization is used, the rubber-like polymer is graft-polymerized with the vinyl monomer to obtain a latex of the graft copolymer resin. The latex of the graft copolymer resin is solidified by a known method, and is washed, dehydrated, and dried to obtain a powder of the graft copolymer resin.
[0029] Examples of the thermoplastic resin include polystyrene, styrene-acrylonitrile copolymer, styrene-methyl methacrylate copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, styrene-maleimide copolymer, rubber-reinforced polystyrene (HIPS), acrylonitrile-butadiene-styrene resin (ABS resin), acrylonitrile-ethylene propylene-styrene resin (AES resin), methyl methacrylate-butadiene-styrene resin (MBS resin), acrylonitrile-n-butyl acrylate-styrene resin (AAS resin), polycarbonate, polyamide, polybutylene terephthalate, polyethylene terephthalate, and polyphenylene oxide.
[0030] The content of the graft copolymer resin in the thermoplastic resin composition is not particularly limited and can be appropriately adjusted taking into consideration the types of the graft copolymer resin and the thermoplastic resin, etc., and can be, for example, 10 to 50 mass% based on the total amount of the thermoplastic resin composition.
[0031] The thermoplastic resin composition can be obtained in the form of pellets by melt kneading using a known device such as a Banbury mixer, a roll mill, or a twin-screw extruder. The obtained thermoplastic resin composition can be appropriately blended with a plasticizer, a lubricant, a flame retardant, a pigment, a filler, a fiber reinforcement, etc. as necessary. The thermoplastic resin composition thus obtained can be molded by injection molding, extrusion molding, compression molding, injection compression molding, blow molding, etc.
[0032] When a mixed solvent of hexane and ethanol (mass ratio 1:1) is dropped onto a molded article formed from the thermoplastic resin composition of this embodiment, the contact angle 0.2 seconds after dropping is 15 degrees or more. By satisfying this requirement, the solvent resistance of the thermoplastic resin composition is improved. From the viewpoint of further improving the solvent resistance, the contact angle is preferably 16 degrees or more, and more preferably 17 degrees or more. The upper limit of the contact angle 0.2 seconds after dropping is not particularly limited, but can be, for example, 30 degrees or less.
[0033] The contact angle 0.2 seconds after dropping can be adjusted to fall within the above range, for example, by reducing the gel content in the rubber polymer, introducing an alkyl (meth)acrylate ester as a vinyl monomer used in graft polymerization, or increasing the amount of an emulsifier having an aromatic ring.
[0034] When a mixed solvent of hexane and ethanol (mass ratio 1:1) is dropped onto a molded article formed from the thermoplastic resin composition of this embodiment, the difference between the contact angle 0.2 seconds after dropping and the contact angle 10 seconds after dropping is preferably 12 degrees or more from the viewpoint of further improving the solvent resistance. The upper limit of the difference between the contact angle 0.2 seconds after dropping and the contact angle 10 seconds after dropping is not particularly limited, but can be, for example, 25 degrees or less.
[0035] The difference between the contact angle 0.2 seconds after dropping and the contact angle 10 seconds after dropping can be adjusted to the above range, for example, by reducing the gel content in the rubber-like polymer, introducing an alkyl (meth)acrylate ester as a vinyl monomer used in graft polymerization, or the like.
[0036] The method for forming a molded article from the thermoplastic resin composition is not particularly limited, but includes a method of melt-kneading the graft copolymer resin and the thermoplastic resin, and then molding by hot pressing.Specifically, for example, the method described in the examples below can be applied.The shape of the molded article is not particularly limited as long as it can be placed in a device capable of measuring the contact angle. EXAMPLES
[0037] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Note that percentages shown in the examples are based on mass.
[0038] [Production of crosslinked butyl acrylate rubber latex (a-1)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixed solution of 85 parts by weight of butyl acrylate and 0.60 parts by weight of allyl methacrylate and an emulsifier aqueous solution of 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-1).
[0039] [Production of crosslinked butyl acrylate rubber latex (a-2)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.011 parts by weight of t-dodecyl mercaptan, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 85 parts by weight of butyl acrylate, 0.60 parts by weight of allyl methacrylate, and 0.189 parts by weight of t-dodecyl mercaptan, and an emulsifier aqueous solution in which 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-2).
[0040] [Production of crosslinked butyl acrylate rubber latex (a-3)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 0.165 parts by weight of styrene, 0.11 parts by weight of acrylonitrile, 5.225 parts by weight of butyl acrylate, 0.0352 parts by weight of allyl methacrylate, 0.0198 parts by weight of ethylene glycol dimethacrylate, 0.375 parts by weight of disproportionated potassium rosinate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 2.835 parts by weight of styrene, 1.89 parts by weight of acrylonitrile, 89.775 parts by weight of butyl acrylate, 0.6048 parts by weight of allyl methacrylate, and 0.3402 parts by weight of ethylene glycol dimethacrylate, and an emulsifier aqueous solution in which 2.125 parts by weight (solid content equivalent) of disproportionated potassium rosinate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was heated to 70°C and aged for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-3).
[0041] <Gel content measurement method> The gel content of the crosslinked butyl acrylate rubber latexes (a-1) to (a-3) was measured by the following method. After drying the above-mentioned crosslinked butyl acrylate rubber latex, 0.25 g was immersed in 100 ml of toluene for 48 hours, filtered through a 300 mesh wire net, and the filtration residue was completely dried. The weight (W0) before and after immersion in toluene and the weight (W1) of the completely dried filtration residue were measured, and the gel content was calculated from the following formula. The results are shown in Table 1. (W1 / W0) x 100 = gel content [%]
[0042] [Table 1]
[0043] [Production of Graft Copolymer Resin (A-1)] Into a nitrogen-purged glass reactor, 50 parts by weight (solid content equivalent) of crosslinked butyl acrylate rubber latex (a-1) was charged and nitrogen-purged. After nitrogen-purging, the temperature inside the tank was raised to 60°C, and an aqueous solution of 0.40 parts by weight of glucose, 0.025 parts by weight of anhydrous sodium pyrophosphate, and 0.001 parts by weight of ferrous sulfate dissolved in 9.0 parts by weight of deionized water was added. After reaching 65°C, a mixture of 13 parts by weight of acrylonitrile (ACN), 37 parts by weight of styrene (STY), and 0.1 parts by weight of t-dodecyl mercaptan and an aqueous emulsifier solution of 1.0 parts by weight of potassium oleate and 0.28 parts by weight of t-butyl hydroperoxide (solid content equivalent) dissolved in 16 parts by weight of deionized water were continuously dropped over 6 hours. After dropping, the mixture was held for 2 hours to obtain graft copolymer resin (A-1).
[0044] [Production of Graft Copolymer Resin (A-2)] Graft copolymer resin (A-2) was produced in the same manner as in the production of graft copolymer resin (A-1), except that 50 parts by weight of crosslinked butyl acrylate rubber latex (a-2) was used instead of the crosslinked butyl acrylate rubber latex (a-1), and a mixed liquid containing 11.7 parts by weight of acrylonitrile, 33.3 parts by weight of styrene, 5 parts by weight of butyl acrylate (BA) and 0.1 parts by weight of t-dodecyl mercaptan was used as the mixed liquid.
[0045] [Production of Graft Copolymer Resin (A-3)] Into a nitrogen-purged glass reactor, 50 parts by weight (solid content equivalent) of crosslinked butyl acrylate rubber latex (a-3) was charged and nitrogen-purged. After nitrogen-purging, the temperature in the tank was raised to 65°C, and an aqueous solution of 0.40 parts by weight of lactose, 0.025 parts by weight of anhydrous sodium pyrophosphate, and 0.001 parts by weight of ferrous sulfate dissolved in 9.0 parts by weight of deionized water was added. After reaching 70°C, a mixture of 12.5 parts by weight of acrylonitrile and 37.5 parts by weight of styrene and an emulsifier aqueous solution of 1.0 parts by weight of disproportionated potassium rosinate and 0.28 parts by weight of t-butyl hydroperoxide (solid content equivalent) dissolved in 16 parts by weight of deionized water were continuously dropped over 6 hours. After dropping, the mixture was held for 2 hours to obtain graft copolymer resin (A-3).
[0046] [Production of Graft Copolymer Resin Powder (B-1)] Deionized water was charged into a single-tank coagulation tank equipped with an agitator blade so that the slurry concentration would be 18% when 100 parts by weight of graft copolymer resin (solid content equivalent) was added to the tank. Then, 4.0 parts by weight of magnesium sulfate was added and the temperature was raised to 85°C. After reaching 85°C, 100 parts by weight of graft copolymer resin (A-1) and 1.3 parts by weight of disproportionated potassium rosinate were added. After the addition, the temperature was raised to 95°C and held for 1 minute, followed by washing with water, dehydration, and drying in a hot air dryer at 90°C for 14 hours to obtain graft copolymer resin powder (B-1).
[0047] [Production of Graft Copolymer Resin Powders (B-2) to (B-3)] Graft copolymer resin powders (B-2) to (B-3) were produced in the same manner as in the production of graft copolymer resin (B-1) above, except that graft copolymer resins (A-2) to (A-3) were used instead of graft copolymer resin (A-1).
[0048] [Production of Graft Copolymer Resin Powder (B-4)] Deionized water was charged into a single-tank coagulation tank equipped with an agitator so that the slurry concentration would be 18% when 100 parts by weight of the graft copolymer was added to the tank in solid content equivalent. Then, 4.0 parts by weight of magnesium sulfate was added and the temperature was raised to 85°C. After reaching 85°C, 100 parts by weight of graft copolymer resin (A-1) and 5.3 parts by weight of disproportionated potassium rosinate were added. After the addition, the temperature was raised to 95°C and held for 1 minute, followed by washing with water, dehydration, and drying in a hot air dryer at 90°C for 14 hours to obtain graft copolymer resin powder (B-4).
[0049] [Production of Copolymer (C-1)] A copolymer (C-1) consisting of 74.5 parts by weight of styrene and 25.5 parts by weight of acrylonitrile was obtained by a known bulk polymerization method. The reduced viscosity of the obtained copolymer (C-1) was measured by the following method, and the reduced viscosity was 0.62 dl / g. Dissolve in N,N-dimethylformamide to give a solution with a concentration of 0.4 g / 100 ml, and measure the flow time at 30°C using a Cannon-Fenske viscometer to determine the reduced viscosity.
[0050] (Evaluation of Graft Copolymer Resin Powder) The graft copolymer resin powders (B-1) to (B-4) and copolymer (C-1) were mixed in the amounts shown in Table 2, and then melt-kneaded at 240°C using a 40 mm twin-screw extruder and pelletized to obtain pellets of a thermoplastic resin composition. From the obtained pellets, various molded products were molded using an injection molding machine set at 250°C, or test pieces were prepared using a press machine, and each measurement and evaluation was performed using the methods shown below. The results are shown in Table 2.
[0051] <Contact angle measurement method> Using the pellets, a test piece measuring 10 cm long x 2 cm wide x 0.2 cm thick was prepared using a press, and the contact angle was measured three times by the sessile drop method using an automatic contact angle meter DMo-501 (manufactured by Kyowa Interface Science Co., Ltd.) 0.2 seconds after the solvent droplet was applied to the test piece and 10 seconds after the solvent droplet was applied, and the average value was calculated. The contact angle was defined as the angle between the applied droplet and the test piece. The solvent used was hexane / ethanol = 1 / 1 (weight ratio). The amount of liquid dropped was 0.5 μl, and a Teflon 22G needle was used as the dropping needle.
[0052] <Impact resistance> The pellets were used to mold various test pieces in accordance with ISO294, and the impact resistance (unit: kJ / m 2 Specifically, the notched Charpy impact value was measured at a thickness of 4 mm in accordance with ISO179.
[0053] <Liquidity> Using the above pellets, the melt volume flow rate (MVR) (unit: cm) was measured at 220℃ and a load of 10 kg in accordance with ISO1133. 3 / 10 min) was measured.
[0054] <Solvent resistance evaluation> Using the above pellets, a test piece measuring 10 cm long x 2 cm wide x 0.2 cm thick was made using a press. For evaluation, a solvent was applied to the side where the test piece was fixed using a cantilever jig, and a load of 600 g was applied to the other side, which was observed for 3 minutes, and evaluation was performed according to the following criteria. Hexane / ethanol = 1 / 1 (weight ratio) was used as the solvent. ○: Not broken ×:Break
[0055] [Table 2]
Claims
1. A thermoplastic resin composition comprising a graft copolymer resin obtained by graft polymerizing an aromatic vinyl monomer and a vinyl monomer including butyl acrylate onto a rubber-like polymer including a (meth)acrylic acid ester-derived structural unit, and a thermoplastic resin, when a mixed solvent of hexane and ethanol (mass ratio 1:1) is dropped onto a molded article formed from the thermoplastic resin composition, the contact angle 0.2 seconds after the dropping is 15 degrees or more; A thermoplastic resin composition, wherein the content of butyl acrylate in the vinyl monomers is 5 to 30 mass % based on the total amount of the vinyl monomers.
2. The thermoplastic resin composition according to claim 1, wherein a difference between the contact angle 0.2 seconds after the dropping and the contact angle 10 seconds after the dropping is 12 degrees or more.
Citation Information
Patent Citations
Thermoplastic resin composition
JP1995011096A
Thermoplastic resin composition
JP1995173361A
Thermoplastic resin composition
JP1996113689A
Thermoplastic resin composition
JP1996113690A
Rubber-reinforced vinyl polymer and thermoplastic polymer composition
JP1997003142A
